Ontology for facebook in relation to Ibn Khaldun ethics: a systematic review - Mohamed Najid, Mohamad Hafizuddin; Zulkifli, Zahidah; Othman, Roslina (The Turkish Online Journal of Design, Art and Communication (TOJDAC), 2018)
Social networking sites (SNS) especially Facebook become a popular platform for sharing and communicate with people all around the world. Its popularity is rising together with the ethical issues that need to be faced by normal users. Since these issues have gotten the people intention, the aim of this paper is to provide an overview of the ontology of Facebook in relation to Ibn Khaldun ethics. A systematic literature review of the articles been conduct related with ontology in Facebook and Ibn Khaldun thoughts which met the following selection criteria: (1) published in a peer-reviewed journal, (2) written in English, (3) free accessed download article, (4) range date from 2008 to 2017, (5) article content related to search topic. The literature search generated 172,731 records of article searched from selected 4 databases from IIUM library website and only 2,235 article titles or abstracts have been screened, which match with author’s keywords. After refined the results, 84 abstract and full-text articles were retrieved and reviewed. The findings identify types of articles by classes in eight categories, namely: (1) author name, (2) year of publication, (3) research methodology being used, (4) retrieved from which database, (5) the area covered by the article, (6) journal name, (7) journal ranking by Scopus, (8) journal subject. In conclusion, the contribution of ontology development between Ibn Khaldun’s thoughts may relate to ethical issues on Facebook, and thus will be a guideline for others researcher to review a model for developing ontology concepts for ethics to extend to broader areas.